Degradation of Ciprofloxacin by Basidiomycetes and Identification of Metabolites Generated by the Brown Rot Fungus Gloeophyllum striatum - Wetzstein, Heinz-Georg (American Society for Microbiology, 1999)
Ciprofloxacin (CIP), a fluoroquinolone antibacterial drug, is widely used in the treatment of serious infections in humans. Its degradation by basidiomycetous fungi was studied by monitoring (14)CO(2) production from [(14)C]CIP in liquid cultures. Sixteen species inhabiting wood, soil, humus, or animal dung produced up to 35% (14)CO(2) during 8 weeks of incubation. Despite some low rates of (14)CO(2) formation, all species tested had reduced the antibacterial activity of CIP in supernatants to between 0 and 33% after 13 weeks. Gloeophyllum striatum was used to identify the metabolites formed from CIP. After 8 weeks, mycelia had produced 17 and 10% (14)CO(2) from C-4 and the piperazinyl moiety, respectively, although more than half of CIP (applied at 10 ppm) had been transformed into metabolites already after 90 h. The structures of 11 metabolites were elucidated by high-performance liquid chromatography combined with electrospray ionization mass spectrometry and (1)H nuclear magnetic resonance spectroscopy. They fell into four categories as follows: (i) monohydroxylated congeners, (ii) dihydroxylated congeners, (iii) an isatin-type compound, proving elimination of C-2, and (iv) metabolites indicating both elimination and degradation of the piperazinyl moiety. A metabolic scheme previously described for enrofloxacin degradation could be confirmed and extended. A new type of metabolite, 6-defluoro-6-hydroxy-deethylene-CIP, provided confirmatory evidence for the proposed network of congeners. This may result from sequential hydroxylation of CIP and its congeners by hydroxyl radicals. Our findings reveal for the first time the widespread potential for CIP degradation among basidiomycetes inhabiting various environments, including agricultural soils and animal dung.